Evaluating Socio-Ecological Interactions for the Management of Protected Urban Green Spaces - Zambrano, Luis; Cano-Santana, Zenón; Wegier, Ana; Arroyo-Lambaer, Denise; Zúñiga-Vega, J. Jaime; Suárez, Antonio; Bouchain, César Rafael; Gual Sill, Fernando; Campo, Julio; Ortega-Larrocea, Pilar; Fonseca, Alejandra; Ramos, Alejandra G.; et al. (Frontiers in Environmental Science, 2019)
Protected urban green spaces (PUGS) are exposed to numerous disturbances and threats since they are immersed in highly dynamic socio-ecological systems. PUGS in highly urbanized cities require particular conservation strategies. Here, we propose an approach for PUGS management which integrates three components: (i) scientific knowledge (monitoring/restoration), (ii) community interaction with the environment, and (iii) management decision. Based on the perception of stakeholders, we searched for evidence that these components are well-integrated in PUGS management and decision-making. The intersection of these components should produce a solid management program, provided that the obtained multidisciplinary knowledge meets the needs of information required by the community and decision makers. We tested this in a small PUGS located within Mexico City at the National Autonomous University of Mexico campus that holds the Ecological Reserve of Pedregal de San Ángel. Through a participatory approach we elicited mental models and represented group beliefs using Fuzzy Cognitive Mapping (FCM). This, in turn, produced evidence of effective integration of the three components in terms of management and decision-making. Our findings provide insight into the actors' perceptions and concerns and suggest that the interactions among the three components, although important, are not self-generated and must be constructed. The findings also suggest that one of the management problems is the mismatch between scientific knowledge and conservation programs. It is paramount to include generated knowledge into management and monitoring programs. The complexity of the PUGS requires an active collaboration among actors and monitoring the development of management strategies using the three components while taking the conservation goals into account.